Infigratinib Reduces Fibroblast Growth Factor 23 (FGF23) and Increases Blood Phosphate in Tumor‐Induced Osteomalacia - Iris R. Hartley; Kelly L. Roszko; Xiaobai Li; Karen Pozo; Jamie Streit; Jaydira delRivero; M. Teresa Magone; Michaele R. Smith; Roo Vold; Carl L. Dambkowski; Michael T. Collins; Rachel I. Gafni (JBMR Plus, 2022)
ABSTRACT Tumor‐induced osteomalacia (TIO) is a rare paraneoplastic syndrome caused by ectopic production of fibroblast growth factor 23 (FGF23) by phosphaturic mesenchymal tumors (PMTs). Acting on renal tubule cells, excess FGF23 decreases phosphate reabsorption and 1,25‐dihydroxy‐vitamin D (1,25D) production, leading to hypophosphatemia, impaired bone mineralization, pain, and fractures. Fibronectin 1‐fibroblast growth factor receptor 1 (FN1‐FGFR1) gene fusions have been identified as possible drivers in up to 40% of resected PMTs. Based on the presumptive role of FGFR1 signaling by chimeric FN1‐FGFR1 proteins, the effectiveness of infigratinib, a FGFR1‐3 tyrosine kinase inhibitor, was studied in an open‐label, single‐center, phase 2 trial. The primary endpoint was persistent normalization of blood phosphate and FGF23 after discontinuation. Four adults with TIO (two nonlocalized, two nonresectable PMTs) were treated with daily infigratinib for up to 24 weeks. All patients had a favorable biochemical response that included reduction in intact FGF23, and normalization of blood phosphate and 1,25D. However, these effects disappeared after drug discontinuation with biochemistries returning to baseline; no patients entered biochemical remission. In the two patients with identifiable tumors, 68Gallium (68Ga)‐DOTATATE and 18Fluoride (18F)‐Fluorodeoxyglucose (FDG) PET/CT scans showed a decrease in PMT activity without change in tumor size. Patients experienced mild to moderate, treatment‐related, dose‐limiting adverse events (AEs), but no serious AEs. Three patients had dose interruptions due to AEs; one patient continued on a low dose for the entire 24 weeks and one patient stopped therapy at 17 weeks due to an AE. The study closed early due to a failure to meet the primary endpoint and a higher‐than‐expected incidence of ocular AEs. Infigratinib treatment lowered FGF23, increased blood phosphate, and suppressed PMT activity, confirming the role of FGFR signaling in PMT pathogenesis. However, treatment‐related AEs at efficacy doses and disease persistence on discontinuation support restricting the use of infigratinib to patients with life‐limiting metastatic PMTs. © 2022 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research. This article has been contributed to by U.S. Government employees and their work is in the public domain in the USA.